Small Farmers' Associations and Agricultural Productivity, Cases from Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
by Hartmut Schneider. Development Centre Papers series. This report is part of the Development Centre research programme into small farmers organisations and productivity. This programme was initiated in the summer of 1985, and the research carried...